2020
DOI: 10.1108/lodj-04-2019-0181
|View full text |Cite
|
Sign up to set email alerts
|

The link between transformational leadership and work-related performance: moderated-mediating roles of meaningfulness and job characteristics

Abstract: PurposeBased on the job characteristics theory (Oldham and Hackman, 2010), the authors highlighted the mediating role of job meaningfulness as a critical psychological state. Employees' positive perception of job meaningfulness could maximize organizational positive outcomes based on task orientation and trustful relationship-based satisfying behaviors. The purpose of this paper is to examine the structural relations among transformational leadership, job characteristics, job meaningfulness and task-related jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 55 publications
(80 reference statements)
6
52
1
3
Order By: Relevance
“…The outcomes show that transformational leadership does indeed (Yammarino & Dubinsky, 1994) because it contributes to strengthening their consciousness, interest and trust, and to motivate staff to improve their work, so that they can give their best to achieve the objectives of the organization. The outcomes of this research are also in line with the results of research by Han, Oh and Kang (2020), which shows that priests as transformational leaders are able to help workers understand and discover the value of their work and lead them to reach high work performance which in turn lead to enhance organization performance (Van der Voet, 2014;Jensen et al, 2020;Kim et al, 2021); Islam et al, 2021). Priests with transformational leadership style in the church have an important role in determining the effectiveness of the services of the church (Allen, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…The outcomes show that transformational leadership does indeed (Yammarino & Dubinsky, 1994) because it contributes to strengthening their consciousness, interest and trust, and to motivate staff to improve their work, so that they can give their best to achieve the objectives of the organization. The outcomes of this research are also in line with the results of research by Han, Oh and Kang (2020), which shows that priests as transformational leaders are able to help workers understand and discover the value of their work and lead them to reach high work performance which in turn lead to enhance organization performance (Van der Voet, 2014;Jensen et al, 2020;Kim et al, 2021); Islam et al, 2021). Priests with transformational leadership style in the church have an important role in determining the effectiveness of the services of the church (Allen, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…The underlying mechanism behind the relationship between TL and JP is inadequately researched and there is a need to conduct more research studies to uncover this (Wang et al , 2013). It is vital to explore the pertinent factors influencing the link between TL and JP (Han et al , 2020). Also there is a burgeoning interest in examining the mediation effects (Singh and Sarkar, 2019) since research without studying the underlying processes lacks rigor (Matheieu et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Knowing these attributes of job characteristics theory, the leaders can use this information for work with the subordinates to ensure their job satisfaction is intact and positive that can lead them to feel embedded toward their job and organization. Transformational leaders may create meaningful work for their subordinates (Han and Oh, 2020). This meaningfulness of work toward the job leads to organizational commitment (Geldenhuys et al, 2014) and job satisfaction (Duffy et al, 2015).…”
Section: Moderating Impact Of Job Characteristics In the Relationship Between Transformational Leadership And Job Embeddednessmentioning
confidence: 99%
“…Some factors may also significantly be considered for increasing job embeddedness (Shehawy et al, 2018), including leadership styles. Rare studies in the past found the relationship of leaders' behavior in embedding employees (Harris et al, 2011;Pimonratanakan et al, 2017), and the few studies found the leadership style impact for developing job embeddedness. For example, the study of Ferreira (2017) examined the effect of ethical leadership with job embeddedness, and the research of Erkutlu and Chafra (2017) resulted in the significant positive influence of empowering leadership for estimating job embeddedness.…”
Section: Introductionmentioning
confidence: 99%